Faktor-Faktor Risiko Hipertensi Pada Klien Pria di Puskesmas Banjaran Kabupaten Majalengka - Jahidul Fikri Amrullah; Mamat Lukman; Neti Juniarti (Jurnal Medika Cendikia, 2015)
Indicators of health status of a nation is the high life expectancy. In Indonesia, hypertension is a serious problem, as well as high prevalence, it is also caused a very fatal disease such as heart disease, stroke, kidney failure and others that affect the life expectancy. Hypertension is still very high in the region of Majalengka, West Java. Incidence of hypertension in the region is around 6.12%, and the impact of hypertension (complication) is the highest morbidity rate of approximately 48% of the total number existing pain. The purpose of this study is to identify of the risk factors in hypertension suffer for male at Banjaran Public Health Center Majalengka Regency. To achieve these objectives, carried out research that is quantitative descriptive with 87 respondents. Data analysis of univariate data to generate data, such as frequency and percentage that is the description of the risk factors of hypertension. Results showed the risk factors of hypertension is high sodium intake (28.7%), moderate (60.9%), low (10.3%). Heavy smoking (59.8%), moderate (28.7%), mild (8%), non-smokers (3.4%).Type A personality (74.7%), personality type B (25.3%). No exercise (77%), exercise is not ideal (19.5%), sports ideal (3.4%). From the results above, the researcher recommended to increase the promotion and prevention for patients with hypertension to avoid further complication.